SPATIAL DISTRIBUTION, PREVALENCE, AND SEVERITY OF FUNGAL DISEASES AFFECTING BLACK PEPPER CULTIVATION IN CÔTE D'IVOIRE - Kouakou Théodore KOUADIO; Massiata DAGNOGO; Eric-Olivier TIENEBO; Adjoa Marie Joséphine KOUADIA; Nahoulé Armond ADJA; Kouadio Paul Martial KOUAKOU; Kouabenan ABO (Journal of Animal and Plant Sciences, 2024)
Black pepper (Piper nigrum L.) is a globally important spice crop. In recent years, black pepper production has faced challenges due to various factors, including diseases. However, the black pepper cultivation is significant in Côte d’Ivoire, the specific diseases affecting the crop have not been comprehensively characterized. This study aimed to identify and characterize fungal diseases of black pepper in Côte d’Ivoire. Surveys were conducted in major black pepper-growing regions from November 2019 to July 2021. Samples of symptomatic leaves, stems, berries, and soil were collected from black pepper plants in three regions: South, Central, and West Côte d’Ivoire. Black pepper disease prevalence and severity were assessed to identify areas with higher disease incidence. Five primary disease symptoms were observed: white spot, necrotic spot with yellow halo, apical necrosis, large concentric brownish spot, and apical desiccation. White spot had the highest average prevalence (67%), followed by necrotic spot with yellow halo (56.89%). Average black pepper disease severity was most pronounced for white spot (25.34%) and decreased for the other symptoms. Colletotrichum and Fusarium were the predominant fungal genera isolated from diseased black pepper plant tissues. Pathogenicity tests confirmed the causal role of these fungi in black pepper disease development. Principal component analysis and hierarchical cluster analysis of pathogenicity data grouped 200 Colletotrichum and 93 Fusarium isolates into three distinct clusters, respectively. These findings provide a foundation for developing effective disease management strategies for black pepper in Côte d’Ivoire.
Keywords: Piper nigrum L; prevalence; severity; fungal disease; Côte d’Ivoire